Effects of feeding different varieties of faba bean (Vicia faba L.) straws with concentrate supplement on feed intake, digestibility, body weight gain and carcass characteristics of Arsi-Bale sheep - Wegi, Teklu; Tolera, Adugna; Wamatu, Jane; Animut, Getachew; Rischkowsky, Barbara A. (Asian-Australasian Association of Animal Production Societies, 2017)
A study was conducted to evaluate the varietal differences among faba bean straws and also to assess the potentials of faba bean straws supplemented with concentrate fed at the rate 70% straws and 30% concentrate mixture on feed intake, digestibility, body weight gain and carcass characteristics of the animals.Forty yearling Arsi-Bale sheep with initial body weight of 19.85±0.29 kg (mean± standard deviation) were grouped in a randomized complete block design into eight blocks of five animals each based on their initial body weight. Straws included in the study were from Mosisa (T1M), Walki (T2W), Degaga (T3D), Shallo (T4S), and local (T5L) varieties of faba bean and concentrate (2:1 ratio of wheat bran to "noug" seed cake). The experiment consisted of seven days of digestibility and 90 days of feeding trials followed by evaluation of carcass parameters at the end.Local variety had lower (p<0.05) in grain and straw yield compared to improved varieties but higher in crude protein, metabolizable energy contents and in vitro organic matter digestibility. The apparent digestibility of dry matter and crude protein of sheep fed Walki and Mosisa straws were higher than (p<0.05) straws from Shallo varieties. Sheep fed Walki straw had greater (p<0.05) dry matter intake, average daily gain and feed conversion efficiency than sheep fed local and Shallo straws. Slaughter body weight and empty body weight were higher (p<0.05) for sheep fed Mosisa and Walki straws as compared to sheep fed Shallo straws. Apart from this, the other carcass components were not affected (p>0.05) by variety of the faba bean straws.There is significant varietal differences between faba bean straws both in quality and quantity. Similarly, significant variation was observed in feed intake, digestibility, body weight gain and feed conversion efficiency among sheep fed different straws of faba bean varieties with concentrate supplement. Based on these results, Walki and Mosisa varieties could be recommended as pulse crop rotation with cereals in the study area.